The relationship between oestrogen and muscle strength: a current perspective - Elliott-Sale, Kirsty Jayne (Revista Brasileira de Educação Física e Esporte, 2014)
The relationship between muscle strength and oestrogen is ambiguous and is still largely unresolved. The evidence for and against an effect of oestradiol on determinants of muscle function is equivocal and often contradictory. The bulk of the research in this area was performed during the eighties and nineties, using models of reproductive functioning such as; the menstrual cycle, the menopause and hormone replacement therapy, oral contraceptives and in vitro fertilisation treatment, to alter the female hormonal milieu. In the last decade, approximately 15 papers have demonstrated a relationship, both positive and negative, between the concentration of oestrogen and skeletal muscle strength. Conversely, around 20 articles have not shown any influence of oestrogen on a number of strength measures. The majority of these studies were performed using post-menopausal and eumenorrheic females. Most current studies use hormonal assays to confirm oestrogen status, however no recent studies have reported the bioavailable concentration of oestradiol. Similarly, no research in the last 10 years has used in vitro fertilisation treatment or pregnancy as acute and chronic models of supra-physiological changes in sex hormone concentration. Future work should focus on performing meta-analyses on each of the key components of muscle strength in an attempt to elucidate a causal relationship. In addition, models of reproductive functioning that cause the greatest magnitude of change to oestrogen concentration should be used, while controlling as many confounding factors as possible.